The Cytotoxicity and Pro-Apoptotic Effect of Ligustilide (Z-Ligustilide) on MCF-7 Breast Cancer Cells and HDF1BOM Human Fibroblast Cells by Using MTT and Annexin Tests - Saeid Mirzaeian; Khalil Khashei Varnamkhasti (Tehran University of Medical Sciences, 2021)
Background and Aim: Breast cancer is one of the most common types of cancer and the second leading cause of cancer death in women. The effect of ligustilide - isolated from the Kelussia on MCF-7 breast cancer cell line compared with human fibroblast cell line (HDF1BOM) was evaluated in the present study. Materials and Methods: MCF-7 and HDF1BOM cell lines were treated for 48 and 72 hours with different concentrations (0, 50, 100, 150 and 200 mg/ml) of Z-ligustilide ((ligustilide (Z)-3-butylidene-4,5-dihydrophthalide)). Then, bioavailability was analyzed by ELISA reader using MTT kit and Apoptosis was assessed by flow cytometry using an Annexin V-FITC/PI kit in two times. Statistical analysis was accomplished by ANOVA and Huynh-Feldt tests using SPSS and FlowJo software.  Results: The results of MTT test showed reduce bioavailability of MCF-7 cell line in all concentrations (from 70.60% in 50 mg/ml to 6.80% in 200 mg/ml  (for 48 h of treatment), from 61.95% in 50 mg/ml  to 5.84% in 200 mg/ml  (for 72 h of treatment)). Also, the results of the Annexin test showed that the induction of apoptosis is not time and concentration dependent manner, and it had increased in most groups. highest percentage of apoptosis were; 98.3% in 50 mg/ml (for 48 h of treatment), and 97.4 % in 100 mg/ml  (for 72 h of treatment). The results of MTT test showed reduce bioavailability of HDF1BOM cell line in both times compared to the control group (from 97.24% in 50 mg/ml  to 5.97% in 200 mg/ml  (for 48 h of treatment), from 90.93% in 50 mg/ml  to 5.26% in 200 mg/ml (for 72 h of treatment)). Also, according to the results of Annexin, early apoptotic cells show a higher percentage (4.21% in 150 mg/ml (for 48 h of treatment), 1.67% in 200 mg/ml  (for 72 h of treatment)). Ligustilide did not show considerable cytotoxicity in HDF1BOM cells. Conclusion: Due to the fact that ligustilide has an inhibitory effect on the growth, proliferation and invasion of cancer cells by inducting apoptosis, it seems that ligustilide can be used to reduce cell proliferation of breast cancer.